Characterization of a fosA3 Carrying IncC–IncN Plasmid From a Multidrug-Resistant ST17 Salmonella Indiana Isolate - Zhang, Li-Juan; Gu, Xi-Xi; Zhang, Jie; Yang, Ling; Lu, Yue-Wei; Fang, Liang-Xing; Jiang, Hong-Xia (Frontiers in Microbiology, 2020)
The aim of this study was to investigate the characteristics of a fosA3 carrying IncC–IncN plasmid from a multidrug-resistant Salmonella isolate HNK130. HNK130 was isolated from a chicken and identified as ST17 Salmonella enterica serovar Indiana and exhibited resistance to 13 antibiotics including the cephalosporins and fosfomycin. S1 nuclease pulsed-field gel electrophoresis and Southern blot assays revealed that HNK130 harbored only one ∼180-kb plasmid carrying fosA3 and blaCTX–M–14, which was not transferable via conjugation. We further examined 107 Escherichia coli electro-transformants and identified 3 different plasmid variants, pT-HNK130-1 (69), pT-HNK130-2 (15), and pT-HNK130-3 (23), in which pT-HNK130-1 seemed to be the same as the plasmid harbored in HNK130. We completely sequenced an example of each of these variants, and all three variants were IncC–IncN multi-incompatible plasmid and showed a mosaic structure. The fosA3 gene was present in all three and bounded by IS26 elements in the same orientation (IS26-322bp-fosA3-1758bp-IS26) that could form a minicircle containing fosA3. The blaCTX–M–14 gene was located within an IS15DI-ΔIS15DI-iroN-IS903B-blaCTX–M–14-ΔISEcp1-IS26 structure separated from the fosA3 gene in pT-HNK130-1, but was adjacent to fosA3 in pT-HNK130-3 in an inverted orientation. Linear comparison of the three variants showed that pT-HNK130-2 and pT-HNK130-3 resulted from the sequence deletion and inversion of pT-HNK130-1. Stability tests demonstrated that pT-HNK130-1 and pT-HNK130-3 could be stably maintained in the transformants without antibiotic selection but pT-HNK130-2 was unstable. This is the first description of an IncC–IncN hybrid plasmid from an ST17 S. Indiana strain and indicates that this plasmid may further facilitate dissemination of fosfomycin and cephalosporin resistance in Salmonella.